PENGARUH LATIHAN MENENDANG SEMBILAN BOLA KE GAWANG TERHADAP KETEPATAN SHOOTING PADA TIM SSB KUANSING SOCCER SCHOOL - Siswanto, Robi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The problem in this research is that their shooting ability is still belowaverage, and perhaps this is also the reason why they often lose in matches. The aim ofthis research was to determine the effect of training in kicking nine balls into the goal onshooting accuracy on the SSB Kuansing Soccer School team. The method used in thisresearch is the experimental method. The research design carried out in this study was"one group pretest-posttest design". The population in this study was SSB Kuansingsoccer school aged 17 years, totaling 16 people. The sampling technique uses a totalsampling technique where the entire population is sampled, amounting to 16 people. The instrument in this research is the ball shooting test at the target (shooting). The data obtained as a result of the research is quality data through tests before and afterproviding training treatment to kick nine balls into the goal. The conclusion of thisresearch is that there is an effect of training in kicking nine balls into the goal on shooting accuracy in the SSB Kuansing Soccer School team with results (tcount 6.475 > ttable 1.753)..Key Words: Kicking Nine Balls Into The Goal, Shooting Accuracy